POLITICAL PARTIES, PARTY PROGRAMMATICITY AND PARTY SYSTEM IN POST 1991 ETHIOPIA - Gebru, Solomon Gebreyohans (European Scientific Journal, ESJ, 2014)
Ethiopia introduced multi-party system following the 1991 regime change. Consequently, dozens of political parties have been established. However, little has been done with regard to the degree of programmaticity of Ethiopian Political Parties (EPPs); the nature and the type of the party system they are operating. Hence, this research was intended to analyse the level of prorammaticity and typology of EPPs, and the nature and type of the party system that are operating. The study was designed to answer whether EPPs and the party system they are operating are programmatic. Both descriptive and analytical methods were employed and data were analyzed through qualitative approach. The study found that although with a varying degree, major EPPs have programmatic platform. Nevertheless, since all EPPs have been using ethnicity as the main means of political support, and non-of them emerged out of pre-existing civil society organizations, Ethiopia’s party system is not yet programmatic. In terms of the number of parties operating, Ethiopia’s party system is best characterized by dominant party system but also with certain features of one-party system. The study argues that Ethiopia should give special attention to depoliticizing ethnicity sooner than later, including by reopening its constitution for discussion and revisiting its electoral and political parties’ laws.